Biomimetic synthesis of Ag-coated glasswing butterfly arrays as ultra-sensitive SERS substrates for efficient trace detection of pesticides - Shi, Guochao; Wang, Mingli; Zhu, Yanying; Wang, Yuhong; Yan, Xiaoya; Sun, Xin; Xu, Haijun; Ma, Wanli (Beilstein Journal of Nanotechnology, 2019)
In this work, we report a biomimetic synthesis route of 3D Ag nanofilm/glasswing butterfly wing hybrids (Ag-G.b.) by magnetron sputtering technology. The 3D surface-enhanced Raman scattering (SERS) substrate is fabricated from an original chitin-based nanostructure, which serves as a bio-scaffold for Ag nanofilms to be coated on. The novel crisscrossing plate-like nanostructures of 3D Ag-G.b. nanohybrids with thick Ag nanofilms provide a substantial contribution to SERS enhancement. Measuring the SERS performance with crystal violet (CV), the Ag-G.b. nanohybrids with the sputtering time of 20 min (Ag-G.b.-20) shows the highest enhancement performance with an enhancement factor (EF) of up to 2.96 × 107. The limit of detection (LOD) for CV was as low as 10−11 M, demonstrating the ultrahigh sensitivity of the Ag-G.b.-20 substrate. In addition, the Ag-G.b.-20 substrate has an outstanding reproducibility across the entire area with the maximum value of relative standard deviation (RSD) of less than 10.78%. The nanohybrids also exhibit a long-term stability regarding Raman enhancement, as suggested by a duration stability test over a period of 60 days. Importantly, the high-performance Ag-G.b.-20 substrate is further applied as an ultra-sensitive SERS platform for the trace detection of acephate, showing its great potential application in biochemical sensing and food security.
Keywords: Ag nanofilm; glasswing butterfly; pesticide; surface-enhanced Raman scattering (SERS)